A 122 GHz multiprobe reflectometer for dielectric sensor readout in SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (IEEE Compound Semiconductor Integrated Circuits Symposium, 2011)
elib2cris::1512001600,laemmle2011a

A 125-GHz permittivity sensor with read-out circuit in a 250-nm SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2013)
elib2cris::1512001600,laemmle2013a

A 2^9 - 1 up to 25 Gb/s M-Sequence Generator IC for UWB Radar Applications in a Low-Cost SiGe BiCMOS Technology - Lämmle, Benjamin; Wagner, Christoph; Knapp, Herbert; Maurer, Linus; Weigel, Robert (German Microwave Conference, 2009)
elib2cris::1512001600,laemmle2009

A 366 mW Direct Digital Synthesizer at 15 GHz Clock Frequency in SiGe Bipolar Technology - Lämmle, Benjamin; Wagner, Christoph; Knapp, Herbert; Maurer, Linus; Weigel, Robert (Radio Frequency Integrated Circuits Symposium, 2009)
elib2cris::1512001600,laemmle2009a

A 62 GHz reflectometer for biomedical sensor readout in SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (IEEE Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2012)
elib2cris::1512001600,laemmle2012

A 70 to 90 GHz High-Linearity Multi-Band Quadrature Receiver in 0.35 μm SiGe Technology - Nasr, Ismail; Lämmle, Benjamin; Aufinger, Klaus; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2013)
An integrated frequency agile quadrature E-band receiver is presented in this paper. The complete receiver is realized in a commercial 0.35μm SiGe:C technology with an ft=fmax of 170/250GHz. The receiver covers the two point to point communication bands from 71 to 76 GHz and 81 to 86 GHz and the automotive radar band at 77 GHz. A wide tuning range modified Colpitts oscillator provides an LO tuning range > 30%. A two stage constant phase RC polyphase network is implemented to provide wide-band quadrature (IQ) LO signals. The measured phase imbalance of the network stays below 8 over the receiver’s frequency range. In addition the chip includes a wide-band LNA, Wilkinson power divider, down conversion mixers and frequency prescaler. Each of the chip’s receiver I/Q paths shows a measured conversion gain above 19 dB and an input referred 1 dB compression point of -22 dBm. The receiver’s measured noise figure stays below 11 dB over the complete frequency range. Furthermore, the receiver has a measured IF bandwidth of 6 GHz. The complete chip including prescaler draws a current of 230mA from a 3.3V supply, and consumes a chip area of 1628μm x 1528 μm.
elib2cris::1512001600,nasr2013b

A 77 GHz Direction of Arrival Detector System with SiGe Integrated Six-Port Receiver - Vinci, Gabor; Lämmle, Benjamin; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (Radio-Wireless Symposium, 2012)
In this publication the design of a 77 GHz Direction-Of-Arrival (DOA) detector system with an Integrated SiGe six-port receiver and a passive microstrip antenna network is presented. The introduction of the six-port receiver for industrial sensors and automotive radar applications has opened a whole new set of possibilities and implementations. A typical problem though of Millimeter-Wave (MW) integration is the interface between the on-chip circuitry and the off-chip system electronics or passives. The antenna design aspects and interconnections are presented with a layouting analysis as well as a system overview of the DOA detector for a flexible, low-complexity and low-cost solution in microstrip technology.
elib2cris::1512001600,vinci2012a
Keywords: Antenna measurements; Antennas; Automotive engineering; Detectors; Microstrip; Radar; Receivers

A 77-GHz Six-Port Receiver Front-End for High-Precision Angle-of-Arrival Detection - Lämmle, Benjamin; Vinci, Gabor; Maurer, Linus; Weigel, Robert; Kölpin, Alexander (IEEE Journal of Solid-State Circuits, 2012)
In this paper an integrated six-port receiver front-end for angle-of-arrival detection of 77-GHz signals is presented. Applications of the circuit are direction finding, automotive radar calibration, or high precision industrial radar. The measurement principle is based on passive superposition of two incident signals and power detection. The circuit features two input amplifiers, a broadband passive six-port network, and four power detectors. The integrated circuit has a power consumption of 95 mW with 5 V supply voltage. It is fabricated in a 200-GHz fT SiGe bipolar technology and occupies only 1028 × 1128 μm2. The circuit operates in a 3-dB bandwidth from 75 GHz to 84 GHz and has a responsivity of 152 kV/W at 80 GHz. A simple calibration method is proposed and all calibration parameters are calculated for different frequency values.
elib2cris::1512001600,laemmle2012b
Keywords: Antenna measurements; Bandwidth; Couplers; Detectors; Receivers; Radar; Frequency Measurement; bipolar integrated circuits; radio direction-finding; angle-of-arrival detection; automotive radar calibration; Six-Port

A clock synchronization for M-sequence-based ultra-wideband systems - Hamouda, Mohammed; Guarin Aristizabal, Gustavo Adolfo; Gardill, Markus; Lämmle, Benjamin; Weigel, Robert; Kissinger, Dietmar; Ußmüller, Thomas (IEEE Transactions on Microwave Theory and Techniques, 2014)
elib2cris::1512001600,hamouda2014c

A Cross Correlation Based Clock Synchronization up to 10GHz for Ultra-Wideband Sensing Systems - Hamouda, Mohammed; Lämmle, Benjamin; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (IEEE International Microwave Symposium, 2014)
This paper presents a cross correlation based synchronization architecture between the clock of the receiver and the transmitter for ultra-wideband radio systems. The designed architecture is based on M-sequence signals instead of the conventional impulse signals. The M-sequence generator and the analog correlation circuit are fabricated on chip using a low cost 0.25μm 95GHz fmax SiGe-HBT-BiCMOS process technology. The chip is mounted on a printed circuit board (PCB) with a commercial voltage controlled oscillator. The measurement results show a low phase noise of the VCO of -66dBc/Hz at 1KHz offset and an rms jitter of 1.6ps for a 10GHz frequency and a bit rate of 20Gb/s.
elib2cris::1512001600,hamouda2014b
Keywords: UWB

A Differential Pair based Direct Digital Synthesizer MMIC with 16.8 GHz Clock and 488 mW Power Consumption - Lämmle, Benjamin; Wagner, Christoph; Knapp, Herbert; Jäger, Herbert; Maurer, Linus; Weigel, Robert (IEEE Transactions on Microwave Theory and Techniques, 2010)
This paper presents a low-power, high-speed direct digital synthesizer monolithic microwave integrated circuit in a SiGe bipolar technology with 8-bit phase and 6-bit amplitude resolution. The phase-to-amplitude mapping circuit is implemented as a differential pair in saturation. The use of a modern SiGe bipolar technology enables both a low power consumption of 488 mW at a 3.3-V supply and a high clock frequency of 16.8 GHz; here, the maximum output frequency is 8.3344 GHz and the frequency resolution is 65.625 MHz. A spurious-free dynamic range (SFDR) between 47-20 dBc is achieved. First Nyquist zone SFDR, narrowband SFDR, and frequency-modulation measurements of the signal are shown and discussed. The chip is fabricated in a 0.35-??m 200-GHz fT SiGe bipolar technology and occupies only 1128 ?? 1028 ??m2. The chip is mounted on a printed circuit board for measurement.
elib2cris::1512001600,laemmle2010a
Keywords: Ge-Si alloys; bipolar MMIC; clocks; direct digital synthesis; power consumption; Direct digital synthesizer (DDS)

A fully integrated 120-GHz six-port receiver front-end in a 130-nm SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Borngraeber, J.; Scheytt, Christoph; Weigel, Robert; Kölpin, Alexander; Kissinger, Dietmar (2013 IEEE 13th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2013)
A fully integrated six-port receiver front-end at 120 GHz center frequency including a low-noise-amplifier, a passive six-port network, a VCO, and four direct converters is presented in this publication. The overall architecture of the designed six-port receiver is analyzed and fundamental theory of the receiver given. The design of the six-port building blocks is described and measurement results are presented. All circuits have been fabricated in a 0.13μm 300-GHz fT SiGe BiCMOS technology. The fully integrated receiver consumes 85.9 rnA from a 3.3-V supply and occupies an area of 1.03mm2. The receiver includes a VCO with a center frequency of 117.15 GHz, a tuning range of 2.7 GHz, and a phase noise of -86 dBc/Hz at 1 MHz offset. The LNA shows a gain of 12 dB, a 3-dB bandwidth of 30 GHz at a power consumption of 9.2 rnA. The six-port core has a conversion gain of 3.6 dB, a P1dB of -12 dBm, and a power consumption of 28 rnA. The overall receiver shows a conversion gain of 2.4 dB at 120 GHz and P1dB of -17 dBm.
elib2cris::1512001600,laemmle2013

A New Concept for Aligning Automotive Long-Range Radar Modules Based on Wireless Microwave Sensing - Weigel, Robert; Vinci, Gabor; Lämmle, Benjamin; Kölpin, Alexander (Sensor & Test, 2011)
elib2cris::1512001600,weigel2011d

An integrated 125 GHz sensor with read-out circuit for permittivity measurement of liquids - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S International Microwave Symposium, 2012)
elib2cris::1512001600,laemmle2012a

An Integrated 77-GHz Six-Port Receiver Frontend for Angle-of-Arrival Detection - Lämmle, Benjamin; Vinci, Gabor; Maurer, Linus; Kölpin, Alexander; Weigel, Robert (Bipolar/BiCMOS Circuits and Technology Meeting (BCTM) 2011, 2011)
In this publication an integrated six-port receiver front-end for angle-of-arrival detection of 77-GHz signals is presented. Applications of the circuit are direction finding, auto-motive radar calibration, or high precision industrial radar. The measurement principle is based on superposition of two incident signals and power detection. The circuit has two input amplifiers, a broadband passive six-port network, and four power detectors. The integrated circuit has a power consumption of 95mW with 5V supply voltage. It is fabricated in a 200-GHz fT SiGe bipolar technology and occupies only 1028 × 1128 μm2. Functionality is demonstrated by applying two different frequencies at the input ports. A simple calibration method is proposed and all calibration parameters are calculated.
elib2cris::1512001600,laemmle2011b
Keywords: Antenna measurements; Calibration; Detectors; Frequency measurement; Phase measurement; Radar; Six-Port

A Wide-Range 77 GHz Direction of Arrival Detector with Integrated Dual Six-Port Receiver - Vinci, Gabor; Barbon, Francesco; Lämmle, Benjamin; Weigel, Robert; Kölpin, Alexander (International Microwave Symposium (IMS) 2012, 2012)
The six-port Direction Of Arrival (DOA) detector has opened a whole new set of possibilities and implementations for novel industrial sensors and radar applications. Detection ambiguity issues as well as challenging calibration techniques are still the main problems of this technology. In this paper the design of an innovative DOA detector system is presented, addressing especially solutions to the problems mentioned above. The proposed device works at 77 GHz and features an integrated Silicon-Germanium (SiGe) dual six-port receiver. Design issues are addressed as well as an overview of the DOA detector system. The highlights are high accuracy, wide range of DOA detection with no ambiguity issues, flexibility, low-complexity and low-cost.
elib2cris::1512001600,vinci2012d
Keywords: Calibration; Detectors; Microwave Circuits; Receiving Antennas; Silicon Germanium; Six-Port

A wide tuning range high output power 56-74 GHz VCO with on-chip transformer load in SiGe technology - Nasr, Ismail; Lämmle, Benjamin; Knapp, Herbert; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Topical Meeting Silicon Monolithic Integrated Circuits in RF Systems Digest, 2012)
This paper presents a wide tuning range modified Colpitts VCO with high output power. The circuit was fabricated using a lowcost SiGe technology with an ft/fmax of 170/250 GHz. The VCO can be tuned between 56.4 and 73.8 GHz having a tuning range of approx. 27%. The maximum measured output power is +9.4 dBm, and the output power remains above +7.0 dBm over the entire tuning range. The VCO has a minimum phase noise of -95 dBc/Hz, which stays below -88 dBc/Hz over the entire tuning range. On-chip frequency dividers were used to enable easier measurement. A single transformer was designed and used simultaneously for output matching of the VCO and as an output balun. The overall chip draws 112 mA from a 3.3 V supply, where the VCO draws 45 mA of the total current.
elib2cris::1512001600,nasr2012
Keywords: VCO; Transformer; Frequency Dividers; Colpitts; FMCW

Design and Applications of Integrated Millimeter-Wave Six-Port Circuits - Lämmle, Benjamin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)

Design and Breakdown Behavior of 77GHz Variable Gain Power Amplifiers in SiGe- Technology - Borutta, Karl; Lämmle, Benjamin; Wagner, Christoph; Maurer, Linus; Weigel, Robert; Kissinger, Dietmar (European Microwave Conference (EuMC), 2013, 2013)
This paper presents two fully integrated differential programmable power amplifiers for automotive radar applications at 77GHz. The power amplifiers were fabricated in a silicon-germanium technology featuring bipolar transistors with an ft/fmax of 200GHz/250GHz. Measurements have been performed for different temperatures, in particular at -40°, 27° and 125°. A maximum gain of 10 dB is achieved for both amplifiers at room temperature. In addition the breakdown behavior of both amplifiers has been investigated. The building blocks of the amplifiers, which are affected by the breakdown effect had been indentified and design guidelines to avoid breakdown effects in power amplifiers are presented.
elib2cris::1512001600,borutta2013
Keywords: differential amplifiers; electric breakdown; millimetre wave bipolar transistors; millimetre wave power amplifiers; millimetre wave radar; programmable circuits; temperature measurement; Current measurement

Design of an integrated 60 GHz cross-coupled oscillator in SiGe technology - Agethen, Roman; Lämmle, Benjamin; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Semiconductor Conference Dresden, 2011)
This paper presents the design of an integrated fully differential 60GHz voltage controlled oscillator in SiGe technology featuring f t = 200 GHz high speed bipolar HBTs. The VCO is based on a differential Colpitts VCO. The core consumes an average amount of 26mA @ 3.3V supply voltage. The tuning bandwidth is about 12%. The utilized buffer at the output consumes additional 64 mA @ 3.3V and provides an output power of 13dBm over the tuning bandwidth. The phase noise @ 1MHz is less than -75 dBc/Hz.
elib2cris::1512001600,agethen2011a

Design of Gain Optimized Broadband Low Noise Amplifiers at 120 GHz using SiGe Technology - Chakraborty, Abhiram; Kissinger, Dietmar; Lämmle, Benjamin; Hartnagel, Hans; Weigel, Robert (German Microwave Conference, 2010)
This paper presents the design of single-ended, double stage cascode low noise amplifiers at 120 GHz. A design methodology employing three techniques for gain enhancement of the LNA is presented. The effect of traditional emitter - degeneration technique and its feasibility for simultaneous noise and power matching is evaluated at 120 GHz. The LNAs are designed in a 250 GHz fT and 300 GHz fmax 0.13 μm SiGe:C BiCMOS process. By employing the three design techniques the gain of the LNA is improved by almost 3.5 dB. The two stage gain optimized LNA achieves a gain of 24 dB and a noise figure of 7.2 dB. The circuit works with a supply voltage of 3.3 V and consumes less than 40 mW of power.
elib2cris::1512001600,chakraborty2010
Keywords: BiCMOS integrated circuits; Broadband amplifiers; Low-noise amplifiers; Noise figure; wideband amplifiers; cascode low noise amplifier; emitter-degeneration technique; 120 GHz; 250 GHz; 300 GHz; noise matching; SiGe Heterojunction Bipolar Transistor

Design Techniques for Broadband Low Noise Amplifiers at 120GHz in a SiGe BiCMOS Process - Chakraborty, Abhiram; Lämmle, Benjamin; Kissinger, Dietmar (ANALOG'11 Fachtagung Entwicklung von Analogschaltungen mit CAE-Methoden, 2011)
elib2cris::1512001600,chakraborty2011

Directional Couplers from 30 to 140 GHz in Silicon - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kölpin, Alexander; Weigel, Robert (Asia-Pacific Microwave Conference (APMC 2010), 2010)
In this paper directional couplers with reduced size, by lumped elements, inverted microstrip, and broadside coupled lines at 61, 110, and 122 GHz center frequency and up to 156-GHz bandwidth have been designed. The couplers show an isolation up to 40 dB. Different SiGe BiCMOS technologies with 250-nm and 130-nm feature width and 5 to 7 metal layers have been used. The measurement results have been compared to simulation results and good agreement has been observed.
elib2cris::1512001600,laemmle2010c
Keywords: Directional couplers; BiCMOS integrated circuits; SiGe BiCMOS technologies; broadside coupled lines; inverted microstrip; silicon; bandwidth; millimeter wave directional couplers; passive circuits

Fast and accurate design methodology for millimeter-wave integrated circuits (invited) - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (URSI General Assembly Scientific Symposium, 2011)
elib2cris::1512001600,laemmle2011

Future trends of integrated millimeter wave six-port receivers - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kölpin, Alexander; Weigel, Robert (6. Joint Symposium on Opto- and Microelectronic Devices and Circuits (SODC 2010), 2010)
elib2cris::1512001600,laemmle2010b

High speed low power phase accumulators for DDS applications in SiGe bipolar technology - Lämmle, Benjamin; Wagner, Christoph; Knapp, Herbert; Maurer, Linus; Weigel, Robert (Bipolar/BiCMOS Circuits and Technology Meeting, 2009. BCTM 2009. IEEE, 2009)
Two phase accumulators with 10 and 8 bit resolution, 7 and 15 GHz maximum clock rate, and a power consumption of 237 and 302.5 mW for use in direct digital synthesizers are presented. The accumulators are designed to retain phase coherency when a frequency switch is performed and are integrated into a DDS to perform simple measurement. The architecture is described, the circuits analyzed and measurements given. The chips are fabricated in a 0.35 mum 200-GHz fT SiGe bipolar technology and occupy only 1028 times 1128 mum2.
elib2cris::1512001600,laemmle2009b
Keywords: phase accumulator; phase accumulator; SiGe; heterojunction bipolar transistor; frequency synthesizer

Integrated dielectric millimeter-wave sensors for biomedical applications (invited) - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (Analog, 2011)
elib2cris::1512001600,laemmle2011c

Integrated Test Concepts for In-Situ Millimeter-Wave Device Characterization - Kissinger, Dietmar; Nehring, Johannes; Bauch, Andreas; Borutta, Karl; Nasr, Ismail; Lämmle, Benjamin; Weigel, Robert (IEEE 13th International New Circuits and Systems Conference (NEWCAS), 2015)
elib2cris::1512001600,kissinger2015b

Integrated Test for Silicon Front Ends - Kissinger, Dietmar; Lämmle, Benjamin; Maurer, Linus; Weigel, Robert (IEEE Microwave Magazine, 2010)
Silicon-based technologies have enabled the monolithic integration of transceiver circuits with operational frequencies up into the millimeter-wave regime. While high integration relaxes the requirements on RF chip-to-chip interconnects and external circuitry, it imposes serious challenges upon the traceability of failure mechanisms and functional errors of the individual building blocks that comprise the front-end. Additionally, expensive external measurement equipment in combination with complex, error-prone, and time-consuming calibration procedures, necessitates the development of on-chip test modules. It has been shown that a variety of built-in test schemes are currently the topic of research for both the mixed-signal and microwave domain. Solutions for the individual building blocks that will enable direct verification of performance parameters have been presented throughout this article. Current RF transceiver architectures will require a mixture of both paradigms for successful implementation of integrated test strategies. It is the authors' belief that the application of such concepts is a must for future integrated transceiver systems to meet the stringent requirements of time-to-market and low-cost of mass market consumer products.
elib2cris::1512001600,kissinger2010b
Keywords: Circuit testing; Integrated circuit interconnections; Integrated circuit technology; Millimeter wave integrated circuits; Millimeter wave measurements; Millimeter wave technology; Monolithic integrated circuits; Radio frequency; Silicon; Transceivers

Microwave wideband spectroscopy techniques targeting biomedical sensing applications - Nasr, Ismail; Hofmann, Maximilian; Radwan, Ahmed; Lämmle, Benjamin; Fischer, Georg; Kissinger, Dietmar; Weigel, Robert (Joint Symposium on Opto- and Microelectronic Devices and Circuits, 2012)
elib2cris::1512001600,nasr2012b

Millimeter-wave integrated reflectometer architectures for biomedical applications - Kissinger, Dietmar; Lämmle, Benjamin; Nasr, Ismail; Weigel, Robert (IEEE Topical Conference on Biomedical Wireless Technologies, Networks and Sensing Systems, 2013)
elib2cris::1512001600,kissinger2013

SiGe Integrated Broadband Wireless Sensors for Biomedical Applications - Kirchner, Jens; Nehring, Johannes; Guarin Aristizabal, Gustavo Adolfo; Nasr, Ismail; Lämmle, Benjamin; Dietz, Marco; Weigel, Robert; Kissinger, Dietmar; Hagelauer, Amelie Marietta (9th Sin-German Joint Symposium on Opto- and Microelectronic Devices and Circuits (SODC2016), 2016)
elib2cris::1512001600,kirchner2016a

Six-Port Based Direction Finding and Micrometer-Accuracy Displacement Detection - Vinci, Gabor; Barbon, Francesco; Lämmle, Benjamin; Weigel, Robert; Kölpin, Alexander (CST European User Group Meeting (CST EUGM) 2012, 2012)
elib2cris::1512001600,vinci2012c
Keywords: Six-Port

Six-Port Technology for Traffic Safety - Kölpin, Alexander; Vinci, Gabor; Lämmle, Benjamin; Lindner, Stefan; Barbon, Francesco; Weigel, Robert (IEEE Microwave Magazine, 2012)
The market for driver-assistance systems for modern automobiles is rapidly growing. Formerly only provided for the luxury automotive market, these systems are nowadays more and more available for mid- and compact-class vehicles as well. This development is not only limited to the passenger car segment but is also more and more important for commercial vehicles and trucks. Some driving assistance systems have already become mandatory, e.g., the antilock breaking system (ABS). Some governments are currently thinking about requiring automatic distance control by law for heavy trucks. Automatic distance control in combination with an automatic emergency breaking system is one of the rising stars for enhancing traffic safety. Radar- based distance control mostly interacts with cruise control systems and it adapts the speed of the driver's car to the distance to the car or obstacle in front of the vehicle. Furthermore, unavoidable accidents are detected and actions for reducing the effects of the crash are automatically initiated for some systems.
elib2cris::1512001600,koelpin2012b
Keywords: six-port; AoA

Temperature Calibration of a Differential Pair based Direct Digital Synthesizer through Subsampling Spectral Analysis - Lämmle, Benjamin; Wagner, Christoph; Jäger, Herbert; Weigel, Robert (Topical Meeting on Silicon Monolithic Integrated Systems in RF Systems, 2010)
The temperature behavior of a high speed direct digital synthesizer with a maximum clock frequency of 16.8 GHz and a power consumption of 488 mW at room temperature is investigated. The DDS has been manufactured in a 200-GHz ft SiGe bipolar technology and occupies a chip area of 1.15 mm2. A subsampling approach is introduced to analyze the output spectrum of the DDS. A calibration is performed over temperature to improve the spectral performance of the DDS. The calibration is based on a two point measurement and the use of a look-up table. After calibration, the third harmonic is below 53 dBc and a narrow band SFDR is nearly constant at 38 dBc.
elib2cris::1512001600,laemmle2010

The Enhanced Six-Port Architecture: A Measurement Based Proof of Concept - Kölpin, Alexander; Lindner, Stefan; Vinci, Gabor; Lämmle, Benjamin; Weigel, Robert (IEEE Topical Meeting on Wireless Sensors and Sensor Networks, 2012)
In this publication the concept of the enhanced six-port receiver is proven by measurements of a hardware demonstrator. The enhanced six-port architecture has been proposed for simultaneous data reception and angle of arrival estimation with only one receiver front-end. It offers high positioning accuracy and high bandwidth combined with low circuit complexity. Up to now the concept has only been introduced and validated by system simulations. In this publication measurements of a hardware setup will be presented for the first time proving the functionality and performance of this new and promising architecture.
elib2cris::1512001600,koelpin2012
Keywords: enhanced six-port; microwave circuit

The enhanced six-port receiver: A new concept for simultaneous data reception and direction of arrival detection - Kölpin, Alexander; Vinci, Gabor; Lämmle, Benjamin; Weigel, Robert (International Microwave Symposium 2011, 2011)
The key benefits of the six-port receiver architecture, being a special type of direct conversion receivers, are its high bandwidth and low circuit complexity. This concept has been known on the one hand for precise phase measurement applications and on the other hand for complex valued data reception in the millimeter wave region. The work presented here shows a new approach for combining both principles in one six-port receiver. For the first time a method for simultaneous data reception and direction of arrival (DOA) detection will be presented requiring only one enhanced six-port front-end.
elib2cris::1512001600,koelpin2011
Keywords: Ad hoc networks; Antennas; Equations; Microwave Circuits; Microwave Communication; Receivers; Direction of arrival; Six-Port

The Six-Port in Modern Society - Kölpin, Alexander; Vinci, Gabor; Lämmle, Benjamin; Kissinger, Dietmar; Weigel, Robert (IEEE Microwave Magazine, 2010)
Modern wireless sensing and communication systems are often based on high bandwidth and high carrier frequencies. In the range beyond 100 GHz, common receiver architectures, like active homodyne or heterodyne receivers, have an issue with the amplification needed for mixing. Also, high bandwidth is a problem for these systems. In this context, the six-port receiver is a good alternative, just as well as for lowvolume markets. The six-port concept is based on the additive superposition of the two RF input signals using four different relative phases leading to constructive or destructive interaction. The resulting signals are directly downconverted to baseband by diode circuits operated in detector or mixing mode. The complexvalued information can be easily reconstructed from the four baseband voltages. Historic evolution leads from the reflectometer approach for an alternative vector network analyzer to receivers for sensing and communications. A recent topic is the technology gap in automotive workshops for adjusting the long-range radar sensor of a car. Here, the six-port concept as alignment tool is a good choice, because of its excellent phase resolution. Currently, the integration of the six-port receiver on a MMIC for frequencies beyond 100 GHz is the focus of current work and will be intensified in the future. Will the six-port concept replace common active homodyne and heterodyne receivers? No, but it is a serious alternative for millimeter-wave frequencies and ultrahigh-bandwidth applications in wireless sensing and communication systems. This modern concept can tap new markets for both wireless sensors and sensor networks.
elib2cris::1512001600,koelpin2010a
Keywords: Antenna measurements; Bandwidth; Baseband; Digital signal processing; Mobile radio mobility management; Receivers; Wireless sensor networks

Ultra-Wideband Transmitters based on M-Sequences for High Resolution Radar and Sensing Applications - Sewiolo, Benjamin; Lämmle, Benjamin; Weigel, Robert (Sixth Conference on Ph.D. Research in Microelectronics and Electronics, 2010)
In this paper we present a novel ultra-wideband transmitter architecture for high resolution radar and sensing applications up to 30GHz. The concept for pulse compression is based on maximal-length sequences to reduce the peak-to-average power ratio. The proposed transmitter consists of a 29-1 linear feedback shift register (LFSR) to generate the radar signal and a fully differential broadband amplifier. A variable gain control has been implemented to provide high sensitivity and decrease the dynamic range. The presented circuit architecture permits the possibility of upconversion, which drastically increases the operational flexibility of the radar system.
elib2cris::1512001600,sewiolo2010

Wearables with integrated Microwave-Sensors for Internet-of-Things-Applications (IoT) in the sector of health-care: An overview - Dietz, Marco; Guarin Aristizabal, Gustavo Adolfo; Hofmann, Maximilian; Nasr, Ismail; Nehring, Johannes; Lämmle, Benjamin; Schwarzmeier, Andre; Aufinger, Klaus; Hagelauer, Amelie Marietta; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (VDE Kongress 2016: Internet der Dinge, 2016)
elib2cris::1512001600,dietz2016a

Wide-Range, Dual Six-Port based Direction-Of-Arrival Detector - Vinci, Gabor; Barbon, Francesco; Lämmle, Benjamin; Weigel, Robert; Kölpin, Alexander (German Microwave Conference (GeMiC) 2012, 2012)
Direction-Of-Arrival (DOA) detection is a challenge and a demanding task for several applications among industrial sensors and automotive radar where high accuracy, robustness, and low cost are important requirements. The six-port receiver based DOA detector has opened a whole new set of possibilities and implementations due to its accurate phase measurement properties. The DOA detection angle ambiguity issue of the six-port receiver caused by phase measurement periodicity is hereby adressed. A new high resolution dual six-port based detector is presented featuring among the advantages provided by the interferometric principle also an ambiguity-free wide detection range.
elib2cris::1512001600,vinci2012b
Keywords: Calibration; Detectors; Dynamic range; Phase measurement; Radio frequency; Receivers; Schottky diodes; Six-Port